Alimentação, Imunidade e Covid-19 - Cavalcanti, Isabella (2020)
We are going through a COVID-19 pandemic caused by the SARS-CoV-2 virus that resulted in social isolation. That isolation combined with media information can affect the emotional development of people, once they are they see themselves isolated and with little social contact. Aiming at people's psycho-emotional development, we of the Educa Coronavirus Project, we will disseminate content and COVID-19 materials. Educa Coronavirus is composed of professionals, undergraduate and graduate students in health, education and design in areas multidisciplinary. Our team intends to produce materials teaching materials to be shared and used in the popular education.